DISCREPANCIA MARGINAL DE COFIAS EN ZIRCONIO ELABORADAS CON DOS SISTEMAS CAD/CAM (2009)
Purpose: To compare the marginal discrepancy of copings made in zirconium oxide with two systems CAD/CAM.Methods: In vitro marginal discrepancies of two systems CAD/CAM (Procera® and Everest®) for ceramic copings and a control group of gold copings were evaluated and compared. A first one human premolar superior was prepared, duplicate 30 times and divided in three groups. Ten copings by group were made. The measurements of marginal discrepancy were made on the natural tooth, on 20 points distributed randomly around the margin preparation. A 3D microscope video was used with magnification of 200X. Values of average and standard deviation were calculated for the marginal openings. The data were analyzed with analysis of variance of a route ANOVA.Results: mean of the marginal discrepancies and standard deviations of the copings were 29±8.6 um for the control group, 22,31±14.6um for Everest® and 21.55±6.9um for Procera®. Significant differences were not found between the copings of the three groups (P> 0.05).Conclusions: The marginal discrepancies were all within the clinically acceptable standard set at 50-100mm, However, Procera® and Everest® systems showed the smallest marginal discrepancies compared with the copings made in an alloy of medium gold content.